STEREOTIPE PEREMPUAN DAKWAH USTADZ ABDUL SOMAD: PERSPEKTIF REPRESENTASI - Kholifah, Nur; Rolando, Dede Mercy (AL-IDZAAH: Jurnal Dakwah dan Komunikasi, 2020)
Discussions related to women are very important from various perspectives. UAS lecture on YouTube about the number of women who provided more than 100 lectures. The UAS study was sharp, interesting, the comments were smart, straightforward, and easy to digest, making the UAS lecture topic about women much favored by the public. This study wants to answer how women's views in the UAS perspective are based on the concept of language representation and meaning. The method used in this study is a qualitative method with a subjective approach. The object of this study focuses on the opinion about women conveyed by UAS on YouTube. Meanwhile, the theory used is the representation of Stuart Hall's theory which discusses language and meaning. The result of this research is that the lecture delivered by UAS contains points in favor of one gender and raises one gender, both male and female. In a meaningful way, these lecture points can be interpreted as being gender biased or referring to gender statements. Regarding, gender can be categorized into a place that is in the form of stereotypes or bad labeling that handles men or women.